2009
DOI: 10.1039/b813061b
|View full text |Cite
|
Sign up to set email alerts
|

The deformation of flexible PDMS microchannels under a pressure driven flow

Abstract: Poly(dimethylsiloxane) (PDMS) microchannels are commonly used microfluidic structures that have a wide variety of biological testing applications, including the simulation of blood vessels to study the mechanics of vascular disease. In these studies in particular, the deformation of the channel due to the pressure inside is a critical parameter. We describe a method for using fluorescence microscopy to quantify the deformation of such channels under pressure driven flow. Additionally, the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 16 publications
10
155
0
1
Order By: Relevance
“…Fluorescence microscopy has been used as a costeffective method to detect deformation of microchannels from their rectangular moulding [20,12,13,14]. Even tough this technique has allowed for the measurement of the maximal cross-sectional displacement of a microchannel, the inherent uncertainties and noisy measurements produced by this technique do not pro- Figure 9.…”
Section: Deformation Profilesmentioning
confidence: 99%
“…Fluorescence microscopy has been used as a costeffective method to detect deformation of microchannels from their rectangular moulding [20,12,13,14]. Even tough this technique has allowed for the measurement of the maximal cross-sectional displacement of a microchannel, the inherent uncertainties and noisy measurements produced by this technique do not pro- Figure 9.…”
Section: Deformation Profilesmentioning
confidence: 99%
“…Also, scaling analysis has been widely used when the applied flow rates are relatively high. The relative equation for the maximum thickness variation of a microchannel at any given position can be described as 22,23,35 FIG. 4.…”
Section: Dpmentioning
confidence: 99%
“…It was found that when the flow rates were doubled the pressure drop increased by only 55%. Hardy et al 23 introduced an alternative florescence microscopy method with Rhodamine 6G dye which was pumped through microfluidic channels and created the fluorescent intensity difference based on the deformation of the microchannels. They reported a 65% increase in the pressure drop when the flow rates were doubled.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In microfluidics, polydimethylsiloxane (PDMS) is one of the most widely used polymers to manufacture channels because of its transparency at optically visible wavelengths, biocompatibility, low autofluorescence, low cost, deformability and ability to mold easily among other advantages, which make this polymer a good candidate for manufacturing model vessels to study the dynamics of vascular diseases. [27][28][29] In this work, we develop transparent non-Newtonian blood analogues that exhibit rheological behavior under shear and extension very similar to real whole blood. To this end, we first measured the linear viscoelastic properties of real whole blood, the storage (G 0 ) and loss (G 00 ) moduli, using passive microrheology.…”
Section: Introductionmentioning
confidence: 99%